Antigen-specific over-expression of human cartilage glycoprotein 39 on CD4+CD25+ forkhead box protein 3+ regulatory T cells in the generation of glucose-6-phosphate isomerase-induced arthritis. (9th July 2014) - Tanaka, Y; Matsumoto, I; Inoue, A; Umeda, N; Takai, C; Sumida, T
Summary: Human cartilage gp-39 (HC gp-39) is a well-known autoantigen in rheumatoid arthritis (RA). However, the exact localization, fluctuation and function of HC gp-39 in RA are unknown. Therefore, using a glucose-6-phosphate isomerase (GPI)-induced model of arthritis, we investigated these aspects of HC gp-39 in arthritis. The rise in serum HC gp-39 levels was detected on the early phase of GPI-induced arthritis (day 7) and the HC gp-39 mRNA was increased significantly on splenic CD4 + T cells on day7, but not on CD11b + cells. Moreover, to identify the characterization of HC gp-39 + CD4 + T cells, we assessed the analysis of T helper (Th) subsets. As a result, HC gp-39 was expressed dominantly in CD4 + CD25 + forkhead box protein 3 (FoxP3) + refulatory T cells (Treg ), but not in Th1, Th2 or Th17 cells. Furthermore, to investigate the effect of HC gp-39 to CD4 + T cells, T cell proliferation assay and cytokine production from CD4 + T cells using recombinant HC gp-39 was assessed. We found that GPI-specific T cell proliferation and interferon (IFN)-γ or interleukin (IL)-17 production were clearly suppressed by addition of recombinant HC gp-39. Antigen-specific over-expression of HC gp-39 in splenic CD4 + CD25 + FoxP3 + Treg cells occurs in the induction phase of GPI-induced arthritis, and addition of recombinant HC gp-39 suppresses antigen-specific T-cell proliferation and cytokine production, suggesting that HC gp-39 in CD4 + T cells might play a regulatory role in arthritis.